CD4+CD25+FoxP3+ Regulatory Tregs inhibit fibrocyte recruitment and fibrosis via suppression of FGF-9 production in the TGF-β1 exposed murine lung - Peng, Xueyan; Moore, Meagan W.; Peng, Hong; Sun, Huanxing; Gan, Ye; Homer, Robert J.; Herzog, Erica L. (Frontiers in Pharmacology, 2014)
Pulmonary fibrosis is a difficult to treat, often fatal disease whose pathogenesis involves dysregulated TGF-b1 signaling. CD4+CD25+FoxP3+ Regulatory T cells (“Tregs”) exert important effects on host tolerance and arise from naïve CD4+ lymphocytes in response to TGF-b1. However the precise contribution of Tregs to experimentally induced murine lung fibrosis remains unclear. We sought to better understand the role of Tregs in this context. Using a model of fibrosis caused by lung specific inducible overexpression of the bioactive form of the human TGF-b1 gene we find that Tregs accumulate in the lung parenchyma within five days of transgene activation and that this enhancement persists to at least fourteen days. Anti-CD25 Antibody mediated depletion of Tregs causes increased detection of soluble collagen and of intrapulmonary CD45+CD34+Col Ia1 fibrocytes. These findings are accompanied by enhanced local concentrations of the classical inflammatory mediators CD40L, TNF-a, and IL-1a, along with the neuroimmune molecule fibroblast growth factor 9 (FGF-9, also known as “glial activating factor”). FGF-9 expression localizes to structural cells and alveolar macrophages in this model and antibody mediated neutralization of FGF-9 results in attenuated detection of intrapulmonary collagen and fibrocytes without affecting Treg quantities. These data indicate that CD4+CD25+FoxP3+ Tregs attenuate TGF-b1 induced lung fibrosis and fibrocyte accumulation in part via suppression of FGF-9.